Command Strategies in Animated Discourse: A Pragmatic Analysis of Hey Arnold! Episode “Full Moon” - Abdussalam Jabaruddin Yamjirin (Universitas Palangka Raya, 2025)
Animated cartoons transcend mere entertainment, offering a rich linguistic landscape that mirrors real-world interactions. This study investigates the pragmatics of directive speech acts, focusing on command strategies in Hey Arnold!, a series celebrated for its realistic portrayal of childhood social dynamics. The episode